1999
DOI: 10.3758/bf03201213
|View full text |Cite
|
Sign up to set email alerts
|

Order information in short-term memory and time estimation

Abstract: In previous experiments, the amount of interference between time production and visual or memory search tasks was shown not to be related to the level of difficulty of the search task per se, but instead to the amount of processing in short-term memory required in the search task. The first experiment of the present study verified whether the amount of interference between time production and a short-term memory task may be related to the level of difficulty of the short-term memory task. Two versions of a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…Whereas processing temporal information interfered with temporal production in Fortin & Massé's (1999) study, produced intervals were not affected by increasing the number of items to be Temporal order in memory and timing 8 maintained in memory in their temporal order of presentation. This dissociation between the effects of processing and maintenance of information in memory on concurrent time production was investigated thoroughly in a subsequent study; results showed , in which there was no effect of that increasing the number of colors or tone timbres to retain during a time production task had no effect (Field & Groeger, 2004, Experiments 2 and 3) whereas retention of pitch information or tone durations showed load-related effects (Experiments 1 and 4).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Whereas processing temporal information interfered with temporal production in Fortin & Massé's (1999) study, produced intervals were not affected by increasing the number of items to be Temporal order in memory and timing 8 maintained in memory in their temporal order of presentation. This dissociation between the effects of processing and maintenance of information in memory on concurrent time production was investigated thoroughly in a subsequent study; results showed , in which there was no effect of that increasing the number of colors or tone timbres to retain during a time production task had no effect (Field & Groeger, 2004, Experiments 2 and 3) whereas retention of pitch information or tone durations showed load-related effects (Experiments 1 and 4).…”
Section: Introductionmentioning
confidence: 55%
“…Whereas adding digits during time discrimination disturbed timing performance, letter or visual pattern recognition did not. As stated by the authors, the absence of interference from retention tasks in Experiments 2 and 3 may be explained by the fact that these tasks involved passive storage of information essentially, which was shown in previous studies not to affect concurrent timing (Fortin & Massé, 1999; see also Field & Groeger, 2004); , and possibly also of athe relatively low level of task difficulty in those experiments may also have been a factor. There was a slight effect of performing concurrent timing concurrently on recognition errors in the spatial memory task, but disruption of recognition in the visuospatial task was clearly weaker than the corresponding effect of arithmetic on timing.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations